3‐Hydroxyisobutyrate dehydrogenase (HIBADH) deficiency—A novel disorder of valine metabolism. Issue 6 (5th July 2021) - Meyer, Melanie; Hollenbeck, Jana C.; Reunert, Janine; Seelhöfer, Anja; Rust, Stephan; Fobker, Manfred; Biskup, Saskia; Och, Ulrike; Linden, Mechthild; Sass, Jörn Oliver; Marquardt, Thorsten
Abstract: 3‐Hydroxyisobutyric acid (3HiB) is an intermediate in the degradation of the branched‐chain amino acid valine. Disorders in valine degradation can lead to 3HiB accumulation and its excretion in the urine. This article describes the first two patients with a new metabolic disorder, 3‐hydroxyisobutyrate dehydrogenase (HIBADH) deficiency, its phenotype and its treatment with a low‐valine diet. The detected mutation in the HIBADH gene leads to nonsense‐mediated mRNA decay of the mutant allele and to a complete loss‐of‐function of the enzyme. Under strict adherence to a low‐valine diet a rapid decrease of 3HiB excretion in the urine was observed. Due to limited patient numbers and intrafamilial differences in phenotype with one affected and one unaffected individual, the clinical phenotype of HIBADH deficiency needs further evaluation.